Measuring elements of collaborative consumption practice: proposition of a framework - Jéssika Narjara Silva Dantas Garrido; Verônica Macário de Oliveira (Revista Eletrônica de Ciência Administrativa, 2024)
This study aimed to propose a framework with determinant elements for collaborative consumption, to understand how individuals behave regarding sharing practices. Exploratory research with a quali-quantitative approach was conducted through a survey with specialists in studies on collaborative consumption in Brazil, who have publications and works developed on the subject in the last three years, so that they presented contributions anchored in their practical experiences and theoretical. The results were qualitatively categorized and analyzed according to the translation validity technique (face validity and content validity). And quantitatively, analyzes were made based on the weighted average, standard deviation, and Content Validity Index (CVI). Based on the results presented in this study, collaborative consumption is conceptualized as an activity to generate access to tangible and intangible resources activated by sharing, mediated by the use of platforms both in the peer-to-peer relationship and by intermediary companies, through some compensation (monetary or not) and social, environmental, economic and individual factors are relevant and representative to measure the tendency of consumers' behavior to practice collaborative consumption.